Towards the Higher Education 4.0 – Characteristics and Criteria - Huu Duc, Nguyen; Huu Thanh Chung, Nguyen; Xuan Huy, Nghiem; Thi Quynh Lan, Mai; Thi Bich Lieu, Tran; Quang Thuy, Ha; Loc, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 34 No 4, 2018)
Abstract: The higher education responding to the fourth industrial revolution (referred as "university 4.0") in this study is identified as a model of innovation – driven smart university. Here, the innovation is the philosophy, object as well as solutions for growing university’s values; while the concept of smart means the infostructure and technical conditions for running the teaching and learning activities based on advancements of 4.0 technologies. The core features of the innovation - driven smart university are described in the so-called "543" model, which consists of: entrepreneurial education (model “5 in 1”); innovation – driven academic researches; innovative ecosystem (model “4 in 1”); smart university; operating mechanism (model “3 in 1”); int  ernationalization and community responsibilities. The framework with criteria for the "university 4.0" model in accordance with quality assurance and university ranking approaches has been developed. Indicators for meeting these criteria can be used by universities for benchmarking themselves to QS 4-star standards or Top 200 universities in QS Asia university ranking table. Keywords: University 4.0, smart university, innovation-driven university, innovative ecosystem, start-up, entrepreneurial spirit, cyber - physical system. References [1] Klaus Schwab, Cách mạng công nghiệp lần thứ tư, Word Economic Forum. Bản dịch tiếng Việt, NXB Chính trị quốc gia Sự thật. [2] Nguyễn Hữu Đức, Hướng tới mô hình đại học Uniwood, Bản tin Đại học Quốc gia Hà Nội, số Xuân Quý Tỵ, 2013, tr. 22. [3] C.B.J. Ong and T.M.N. Nguyen, The 4Cs Framework to Transform Higher Education Institution as an Innovation Producing Ecosystem, International Workshop “Creativity Development and Opportunities for Business and Startup Ideas”. Hanoi, 11-12,8/2017. [4] Nguyễn Chí Hải, Nguyễn Hồng Nga, Một số đặc điểm của đại học nghiên cứu – Kinh nghiệm quốc tế cần áp dụng tại Việt Nam, Tạp chí Khoa học Trường ĐH Sư phạm Thành phố Hồ Chí Minh, 4 (2005) 150. [5] Nancy W. Gleason, edited, Higher education in the era of the fourth industrial revolotion, Palgrave Macmillan, Singapore, 2018. [6] A. Engovatova and E. Kuznetsov, A plan for the growth of the knowledge economy in Russia, RusianDirect 4 (2016) 8 [7] Trần Thọ Đạt và Doãn Hoàng Minh, Đại học định hướng doanh nghiệp. Tạp chí Kinh tế và Phát triển, 233 (2016) 10-19. [8] S. Case, S.M. Coleman, G. Deshpande et al., The Innovative and Entrepreneurial University: Higher Education, Innovation & Entrepreneurship in Focus. U.S. Department of Commerce, 2013. [9] QS STAR, https://www.topuniversities.com/qs-stars/qs-stars-methodology [10] Scimago Institutions Rankings, https://www.scimagoir.com/ [11] World Economic Forum, The Future of Jobs Employment, Skills and Workforce Strategy for the Fourth Industrial Revolution Executive Summary (2016). [12] Nguyễn Hữu Thành Chung, Xây dựng mô hình đại học đổi mới (sáng tạo) nhằm thích ứng với cuộc CMCN lần thứ 4 (Nghiên cứu trường hợp Đại học Quốc gia Hà Nội), Luận văn Thạc sỹ, Trường Đại học Khoa học Xã hội và Nhân văn, ĐHQGHN, 2018. [13] Nguyễn Hữu Đức, Nghiêm Xuân Huy, Nguyễn Hữu Thành Chung, Nghiên cứu xu thế đổi mới sáng tạo trong cuộc CMCN lần thứ tư bằng phương pháp phân tích trắc lượng thư mục, VNU Journal of Science: Policy and Management Studies, 33(3) (2017) 1-7. [14] Framing Malaysian Higher Education – Future Proof Talents, Ministry of Higher Education Malaysia, 2018. [15] D. Humphreys, Making the Case for Liberal Education – Responding to Challenges, 2006, Association of American Colleges and Universities. [16] R. May Lee, Yanyue Yuan, Innovation Education in China: Preparing Attitudes, Approaches and Intellecetual Environments for Life in the Automation Economy, in: Higher education in the era of the fourth industrial revolotion, Nancy W. Gleason, edit, Palgrave Macmillan, 2018, p. 93. [17] S.M. Drake and R.C. Burns, Meeting Standards Through Integrated Curriculum, Association for Supervision and Curriculum Development, Alexandria, Virginia USA, 2003. [18] Tan Eng Chey, Innovation and Entrprise at National University of Singapore, (2018), private comminication. [19] Douglas Thompson, Technology Transfer and Commercialisation, Reports Minsk, 27th May 2015. http://www.scienceportal.org.by/upload/2015/June/Inconet%20EaP%20-%20Presentation/8%20Thompson_Tech%20Transfer%20and%20Commercialisation.pdf). [20] Research Management and Development Division, Office of President, Mahidol University: Thailand 4.0 and Entrepreneupship University, 2016. http://www.senate.mahidol.ac.th/Data/Academic%2022%20Jul/VP%20Sansanee%20Academician%20Council%20Jul22_2016.pdf [21] Deborah Wince-Smith, Universities are Wellsprings of Innovation, Drivers of Regional Economies, The Global Federation of Competitiveness Councils. A network of leaders committed to accelerating global prosperity through fostering innovation ecosystems, 2017; https://blog.thegfcc.org/universities-are-wellsprings-of-innovation-drivers-of-regional-economies-8a3c097e6cc [22] Kees Eijkel, http://www.successful.com.au/blog/2013/03/29/semip-innovation-showcase-2013/ [23] Kosmas Galatsis, Nanoelectronics Research Gaps and Recommendations, 2017. http://technologyandsociety.org/nanoelectronics-research-gaps-and-recommendations-a-report-from-the-international-planning-working-group-on-nanoelectronics-ipwgn/ [24] Jackson Deborah, What is an Innovation Ecosystem?, National Science Foundation, Arlington, VA (http://erc-assoc.org/docs/innovation_ecosystem.pdf), 2012. [25] P.U. Lijie, Innovation & Entrepreneurship Education at Nanjing University, Asian University Forum, Mogolia, 6 June, 2017. [26] J. Wonglimpiyarat, The innovation incubator, university business incubator and technology transfer strategy: The case of Thailand, Technology in Society 46 (2016) 18–27 [27] Fehmida Hussain, E-learning 3.0 = E-learning 2.0 + Web.3.0, IADIS International Conference on Cognition and Exploratory Learning in Digital Age (CELDA 2012), p.11. [28] Behrad Bagheri, Big future for cyber-physical manufacturing systems, Design World, September 23, 2015 [29] Kuo-Ming Chao, Cyber Physical Systems for Future Higher Education, Coventry University, UK, private communication. [30] H. Etzkowitz and L. Leydesdorff, The Triple Helix – University – Industry - Government Relations: A Laboratory for Knowledge Based Economic Development". Rochester, NY., 1995. [31] Đại học Quốc gia Hà Nội: Hướng dẫn về các tiêu chí đại học nghiên cứu (2013). https://vnu.edu.vn/upload/vanban/2013/10/08/1206-Huong-dan-ve-cac-tieu-chi-truong-dai-hoc-nghien-cuu..pdf [32] U-Multirank: Compare University and Colleges Rankings, https://www.umultirank.org/ [33] SETARA: Overal structure of the SETARA rating 09 instrument, Malaysia http://www.mqa.gov.my/portalmqav3/SETARA09/pdf/DIMENSI%20DOMAIN%20KRITERIA%20%20INDIKATOR%20SETARA%20%2709.pdf [34] Allan Gibb, Exploring the synergistic potential in entrepreneurial university development: towards the building of a strategic framework, Annals of Innovation & Entrepreneurship 3 (2012) 16742. DOI: 10.3402/aie.v3i0.16742 [35] AUN-QA: Hướng dẫn đánh giá cơ sở giáo dục của mạng lưới đảm bảo chất lượng giáo dục các trường đại học ASEAN, NXB ĐHQGHN, 2017.